2015
DOI: 10.2196/jmir.4803
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of “Liking” Three Types of Health and Fitness-Related Content on Social Media: A Cross-Sectional Study

Abstract: BackgroundAdolescence and young adulthood are key periods for developing norms related to health behaviors and body image, and social media can influence these norms. Social media is saturated with content related to dieting, fitness, and health. Health and fitness–related social media content has received significant media attention for often containing objectifying and inaccurate health messages. Limited research has identified problematic features of such content, including stigmatizing language around weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 24 publications
5
78
0
4
Order By: Relevance
“…A quick scan of Facebook also reveals numerous celebrity-endorsed (for example https://www.facebook.com/ 12WBT) or commercial (for example https://www.face book.com/weightwatchers) weight-loss pages. A survey of 15-29-year-olds in Australia measured consumption of three types of health-related social media content on Facebook, Twitter and Instagram, and found that 31% consumed "fitspiration" (fitness inspiration) pages, 14% consumed detox pages, and 23% consumed diet/fitness plan pages (Carrotte & Vella, 2015). Teenage girls made up almost half of all consumers of this type of content.…”
Section: Healthy Eatingmentioning
confidence: 99%
“…A quick scan of Facebook also reveals numerous celebrity-endorsed (for example https://www.facebook.com/ 12WBT) or commercial (for example https://www.face book.com/weightwatchers) weight-loss pages. A survey of 15-29-year-olds in Australia measured consumption of three types of health-related social media content on Facebook, Twitter and Instagram, and found that 31% consumed "fitspiration" (fitness inspiration) pages, 14% consumed detox pages, and 23% consumed diet/fitness plan pages (Carrotte & Vella, 2015). Teenage girls made up almost half of all consumers of this type of content.…”
Section: Healthy Eatingmentioning
confidence: 99%
“…With the increase in the number of social media outlets and time spent on them, the reach of SM is expanding to include younger adolescent girls [22]. In the present study, all adults reported having conversations with teen girls about health body image, and in focus groups, the teenage girls were aware that many ads and posts are photo-shopped or manipulated and that attaining the same physique is often unrealistic.…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, those who are older, female, more active, and in better health are more likely to use social networking sites for health information [5]. Further, consuming (liking or following) health and fitness-related social media content is done predominantly by teenage girls [22]. Many of these findings have come from simple, straight-forward surveys, but the relationship between adolescent girls use of social media and the effects on health behavior is likely complex and multifactorial.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were eligible if they were young adults (aged 18-25; as this age group are key consumers of social media in general [1], and of Fitspiration specifically [5]) who self-defined themselves as followers of Fitspirational content on social media. In contrast to the only other qualitative study on this topic we sampled both males and females.…”
Section: Sampling and Recruitmentmentioning
confidence: 99%
“…Social media users encounter Fitspirational content either deliberately, by linking with and following users known for posting this type of content or inadvertently through the posts and shares of other people already in their network [3]. Carrotte [5] identified young women as key consumers of Fitspiration content.…”
Section: Introductionmentioning
confidence: 99%